An overview of the Italian market for 2015: cooking quality and nutritional value of gluten‐free pasta. (23rd October 2018) - Morreale, Federico; Boukid, Fatma; Carini, Eleonora; Federici, Enrico; Vittadini, Elena; Pellegrini, Nicoletta
Summary: A roundup of gluten‐free (GF) pasta sold in the Italian market in 2015 was characterised throughout cooking behaviour, texture, colour and nutritional value. A preliminary evaluation of cooking quality of the thirty‐three available products underlined an extremely heterogeneous technological quality. Eleven categories were, therefore, discriminated based on the main ingredients declared on the labels. Interestingly, the most numerous category (rice and corn) was pulverised on the factorial space indicating highly heterogeneous properties. This result was confirmed throughout multivariate statistics and can be likely due to diversity in ingredients proportions or/and processing. Nutritional evaluation of GF pasta pointed out a good nutritional quality. Therefore, the combination of technological and nutritional analyses demonstrated a huge difference among the analysed pasta samples, which can increase the difficulty of consumers to make their choice, and leaves room for further improvement of GF pasta formulation and productive processing. Abstract : Given the impressive growth of the gluten‐free market, it is necessary to focus on the quality of the products commercialized. In this frame, the Italian market of gluten‐free pasta was considered as it is one of the largest ones. In this work the cooking quality of the gluten‐free pasta products was addressed to better highlight the characteristics of the pasta that we eat.